High-energy ball milling preparation of La0.7Sr0.3MnO3 and (Co,Ni)Fe2O4 nanoparticles for microwave absorption applications - Anh Xuan, Chu Thi; Bach, Ta Ngoc; Thanh, Tran Dang; Hong Le, Ngo Thi; Manh, Do Hung; Phuc, Nguyen Xuan; Hoai Nam, Dao Nguyen (Vietnam Journal of Chemistry, 2016)
Microwave and radar absorbing materials (MAM and RAM) are widely used for reducing electromagnetic interference (EMI) for electronic equipment and devices, in electromagnetic anechoic technique, and especially in radar stealth technology. Ferromagnetic and ferrimagnetic nanoparticles have been known to have a strong microwave absorbing capability. To study magnetic MAMs and RAMs, we have prepared La0.7Sr0.3MnO3 ferromagnetic and several (Co,Ni)Fe2O4 ferrimagnetic nanoparticle powders using high-energy ball milling technique, which is capable of producing nanoparticles in reasonably larger scale comparing to conventional chemical methods. The magnetic properties of the nanoparticle powders are strongly dependent on the preparation conditions. The milling process produces damages and defects not only on the surface, but also the crystal structure inside the particles, that cause an undesired strong reduction of saturation magnetization (Ms) and an increase of coercivity (Hc). A suitable post-milling heat treatment is able to heal the particles and recover most of their saturation magnetization and magnetic softness. The nanoparticles are then mixed with paraffin for microwave and radar absorption measurements